Implementing Situational Leadership by School Principals to Enhance the Performance of Early Childhood Education Teachers - Wahidaini, Wahidaini; Syam, Aldo Redho; Ikhwan, Afiful; Kurnianto, Rido; Rahman Zh, Miftah Hur (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to describe and analyze the implementation of situational leadership of school principals in improving teacher performance at PAUD Pesantren Anak Sholeh Darul Qur'an Kalianda, Lampung. The research approach used is qualitative descriptive, with data collection through observation techniques, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing which are systematically compiled based on field findings. The results of the study show that the implementation of situational leadership by school principals has a strategic role in increasing the effectiveness of teacher performance and creating a conducive, collaborative, and productive work environment. The implementation of situational leadership is reflected in four main styles, namely: (1) telling, providing clear directions to teachers in the implementation of tasks; (2) selling, encouraging teacher responsibility and motivation without pressure; (3) participating, strengthening teachers' participation in the decision-making process; and (4) delegating, providing trust and delegation of authority according to the capacity of each teacher. Thus, the situational leadership model has proven to be effective and relevant in supporting the management of Islamic educational institutions, especially in facing managerial challenges and teacher professionalism in the era of globalization.